Evaluation of temperature rise in the pulp during various IPR techniques-an in vivo study - Kiran Banga; Nitin Arora; Sridhar Kannan; Ashish Kumar Singh; Abhita Malhotra (SpringerOpen, 2020)
Abstract Background Non-extraction treatment protocol has gained a lot of popularity over extraction for orthodontic treatment. Interproximal enamel reduction is one such method that makes it possible to do orthodontic treatment without extractions. This procedure, which can be done by various techniques, leads to a rise in the temperature of the pulp of the teeth. Previously, studies have been done which have evaluated the temperature changes inside the pulp chamber of extracted teeth, during interproximal enamel reduction. However, no documented literature exists that has evaluated these changes in the live pulp of the teeth whilst interproximal enamel reduction (IPR) is being performed. Therefore, this study aimed to evaluate the temperature changes inside the live pulp of the teeth during various interproximal enamel reduction techniques in vivo. Aims Evaluation of temperature rise in the pulp during various interproximal enamel reduction techniques, done in vivo. Material and method The study was performed on patients for whom extraction of premolars had been advised for their orthodontic treatment. Fifty-one premolar teeth were randomly divided into three groups of IPR, i.e. using airotor and bur, handheld metal strip and orthodontic IPR kit (oscillating system). IPR was performed on the mesial and distal sides after access opening, temperature change was recorded during IPR and the readings were compared. The Shapiro-Wilk test was utilized for checking whether the data satisfied the requirement of normal distribution. Results The highest temperature rise was seen in group 1 in which interproximal enamel reduction was performed using airotor and bur. The minimum temperature rise was observed in group 2 in which interproximal enamel reduction was done using the handheld metal strip, whereas the temperature rise observed in group 3, in which interproximal enamel reduction was done using IPR kit, was between the range of group 1 and group 3. The temperature change was in the following order-group 1 (2.08 °C) > group 3 (1.22 °C) > group 2 (0.52 °C). Conclusion None of the methods used to perform interproximal enamel reduction caused a temperature increase more than 5.5 °C, beyond which pulp necrosis may occur. Therefore, all three methods used in the study for IPR were found to be safe.